Sleep-promoting factor S: purification and properties. - Krueger, J M (1978)
Sleep-promoting factor was purified from acid/acetone extracts of whole brains of rabbits and from brainstems of slaughterhouse cattle. Intraventricular infusion of extracts purified by means of ion exchange and gel filtration induced excess slow-wave sleep in rabbits for 5-10 hr. The procedure is simple and provides material suitable for physiological studies. Further treatment by partition chromatography and electrophoresis yielded an active product that was purified at least 1 million-fold. This product was inactivated by incubation with mixed carboxypeptidases A and B. Amino acid analysis of acid hydrolysates indicated that the effective dose was less than 150 pmol per rabbit and the original concentration in brain tissue was of the order of 30 pmol/g of brain.